Excerpt from Trans-Americanity: Subaltern Modernities, Global Coloniality, and the Cultures of Greater Mexico - Saldívar, José David (eScholarship Publishing, University of California, 2018)
José David Saldívar’s work, excerpted from Trans-Americanity: Subaltern Modernities, Global Coloniality, and the Cultures of Greater Mexico, focuses on Américo Paredes, whom he refers to as a “proto-Chicano.” Here he discusses Paredes’s columns written from Asia for the United States Army magazine Stars and Stripes and how his experience in Asia between 1945 and 1950 crossed with and informed his evolving viewpoint on US–Mexican borderlands and his “outernationalist” envisioning of a “Greater Mexico